Evaluation of risk factors for the recurrence of ovarian endometriomas. (August 2016) - Selcuk, Selcuk; Cam, Cetin; Koc, Nermin; Kucukbas, Mehmet; Ozkaya, Enis; Eser, Ahmet; Karateke, Ates
Abstract: Objectives: To evaluate the risk factors for the recurrence of ovarian endometrioma after laparoscopic cystectomy. Study design: Reproductive aged patients who underwent laparoscopic ovarian endometriotic cystectomy and with histopathologically confirmed diagnosis of ovarian endometrioma were evaluated retrospectively. Histopathologic specimens were reevaluated and histopathologic characteristics of ovarian endometriotic cysts (thickness of cyst wall, thickness of fibrosis [ToF], thickness of ovarian tissue, the number of follicles per cyst, the depth of penetration [DoP] of endometrial tissue into the cyst wall) were determined. Along the determined histopathologic findings, demographic characteristics (age at surgery, number of pregnancies), clinical symptoms (dysmenorrhea, infertility), intraoperative findings (revised American Society for Reproductive Medicine [rASRM] stage), imaging features (bilaterality, cyst diameter), and biochemical parameters (Ca125, Ca19.9, Ca15.3) were evaluated as possible risk factors for the recurrence of endometrioma. The variables with p < 0.2 in univariate analysis were introduced into regression analysis to determine the risk factors for recurrence. Results: There were statistically significant differences in age group (≤35 years and >35 years), the ToF and DoP between patients with recurrence and those with no recurrence. In Cox regression analysis, age ≤35 years and DoP were significant risk factors for presence of recurrence. DoP, ToF, preoperative cyst diameters in ultrasonographic examination were inversely correlated with recurrence interval. In multivariate regression analysis, the DoP was found the only significant risk factor for the recurrence interval. 1.2 mm of DoP was found as the optimum cut off value for presence of recurrence according to Youden index criteria in ROC curve analyze. The sensitivity (62.9%), specificity (75%) were obtained at the cut off value of 1.2 mm for DoP. Conclusion: Histopathological features of ovarian endometriotic cyst may have important roles on predicting the recurrence of the endometrioma. Predicting the recurrence risk of particular patient is very important in future management of the disease. Knowing the recurrence risk of an endometrioma will help in deciding the optimal treatment modalities for each individual patient. High risk patients should be offered appropriate treatments according to the clinical status without delay and low risk patients should be protected from overtreatment.